MARRIED WOMEN AND PAP SMEAR, WHAT THEY KNOW? HOW THEY DO? - M. Jalalvandi; M. Khodadoostan (Iran University of Medical Sciences, 2005)
Cervical Cancer is the most common cancer site of female reproduction system and the second common cancer in women in the world. It is the leading cause of cancer death in women in developing countries. High rate of mortality of women with this fatal disease is thought to be the consequence of the lack of screening programs. This study focused on the knowledge of women about Pap smear and also their performance level.   So, with a descriptive cross-sectional way, 788 women were interviewed and questionnaires were completed.   Finding showed that meanwhile, less than half of the respondents were aware of the procedure, only 17.5% of them had done it regularly or with at least less that 36 months intervals. Also, a meaningful significant relation was found between the knowledge level and the performance of the participants (P<0.001).   To sum up, we strongly recommend strict screening programs for cervical cancer and frequent pap smear for women in all ages. We also, suggest the authorities to provide women with proper educational sessions about reproductive system cancer screening activities.